The Readiness of Business Practitioners in Special District of Yogyakarta in Facing the Operation of New Yogyakarta International Airport 2019 - Bhinadi, Ardito; Sumarli, Ardithama (International Journal of Economics and Financial Issues, 2019)
This research aims to measure the business practitioners’ readiness level in regency/city of Special District of Yogyakarta (DIY) in facing the opportunity of the business and economic development with the operation of New Yogyakarta International Airport (NYIA) and factors to the readiness. The primary data were obtained through the survey of 170 respondents as the samples as the DIY business practitioners. The analysis tools included descriptive statistics, factor analysis and regression. The research results showed the moderate category of business practitioners’ readiness in DIY in facing the operation of NYIA 2019. This was positively and significantly affected by the factors of innovation, business opportunities, optimism, socialization and cost threat. Innovation here had the most significant factor in determining the business practitioner’s readiness in facing the operation of NYIA 2019; while the factors of threat of business continuity and knowledge about NYIA showed no effects statistically towards the business practitioners’ readiness. Keywords: readiness, business practitioners, New Yogyakarta International Airport JEL Classification: D820 DOI: https://doi.org/10.32479/ijefi.8412